The development of business environment dynamics to improve the relationship between network capability and MSME performance - Kumalasari, Riesta Devi; Sudiro, Ahmad; Rofiaty, Rofiaty; Djumahir, Djumahir (Eastern-European Journal of Enterprise Technologies, 2025)
This study focuses on the performance of micro, small, and medium enterprises (MSMEs) in the craft fashion sector in Malang Raya, by examining the influence of network capability on MSME performance and the moderating role of environmental dynamics. The main problem raised is the low performance of MSMEs in this sector, even though the Malang Raya area has great potential with a high number of tourists. MSMEs still face difficulties in utilizing market opportunities due to limited network access and adaptation to environmental dynamics. The results of the study show that network capability significantly improves MSME performance by strengthening access to resources, collaboration, and innovation. In addition, environmental dynamics – such as changes in market demand and the level of competition – moderate this relationship by increasing the impact of network capability on MSME performance. Data analysis shows that MSMEs with strong network capabilities are better able to capture market opportunities through collaboration with suppliers, customers, and strategic partners. Meanwhile, high environmental dynamics encourage flexibility and innovation in product development, thereby strengthening network effectiveness and increasing competitiveness. The uniqueness of this research result lies in the finding that the synergy between network capability and environmental adaptation enables MSMEs to overcome market barriers and increase profitability. This finding is relevant not only for the craft fashion sector in Malang Raya but also for other creative economy sectors with dynamic market conditions. Implementation of this result requires MSME investment in business network development as well as government policy support that encourages collaboration and training